ECB-Global 2.0: A global macroeconomic model with dominant-currency pricing, tariffs and trade diversion - Georgios Georgiadis; Sebastian Hildebrand; Martino Ricci; Ben Schumann; Björn van Roye (European Central Bank (ECB), 2021)
In a highly interlinked global economy a key question is how foreign shocks transmit to the domestic economy, how domestic shocks affect the rest of the world, and how policy actions mitigate or amplify spillovers. For policy analysis in such a context global multi-country macroeconomic models that allow a structural interpretation are needed. In this paper we present a revised version of ECB-Global, the European Central Bank's global macroeconomic model. ECB-Global 2.0 is a semi-structural, global multi-country model with rich channels of international shock propagation through trade, oil prices and global financial markets for the euro area, the US, Japan, the UK, China, oil-exporting economies, Emerging Asia, and a rest-of-the-world block. Relative to the original version of model, ECB-Global 2.0 features dominant-currency pricing, tariffs and trade diversion. We illustrate the usefulness of ECBGlobal exploring scenarios motivated by recent trade tensions between China and the US.
Keywords: C51; E30; E50; 330; Macro-modelling; multi-country models; spillovers